1998
DOI: 10.1016/s0167-4889(97)00114-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulation of primary human keratinocytes by prostaglandin E receptor EP2 and EP3 subtypes

Abstract: We examined the contribution of specific EP receptors in regulating cell growth. By RT-PCR and northern hybridization, adult human keratinocytes express mRNA for three PGE2 receptor subtypes associated with cAMP signaling (EP2, EP3, and small amounts of EP4). In actively growing, non-confluent primary keratinocyte cultures, the EP2 and EP4 selective agonists, 11-deoxy PGE1 and 1-OH PGE1, caused complete reversal of indomethacin-induced growth inhibition. The EP3/EP2 agonist (misoprostol), and the EP1/EP2 agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 53 publications
12
85
2
Order By: Relevance
“…The EP 4 antagonist caused an early S-phase arrest of 3T6 fibroblasts, whereas the EP 1 antagonist-treatment of these cells was associated with a significant increase in G 0 /G 1 population with respect to control cells. However, we cannot rule out the presence of EP 2 or EP 3 receptors in 3T6 fibroblasts and their contribution to the control of their growth, because it has been described in other cell types (18,24). The hypothesis that PGE 2 regulates the cell cycle at different levels by interacting with specific subtype receptors also was supported by the data on the effect of AH-6809 and AH-23848B on cyclin levels.…”
Section: Discussionmentioning
confidence: 77%
“…The EP 4 antagonist caused an early S-phase arrest of 3T6 fibroblasts, whereas the EP 1 antagonist-treatment of these cells was associated with a significant increase in G 0 /G 1 population with respect to control cells. However, we cannot rule out the presence of EP 2 or EP 3 receptors in 3T6 fibroblasts and their contribution to the control of their growth, because it has been described in other cell types (18,24). The hypothesis that PGE 2 regulates the cell cycle at different levels by interacting with specific subtype receptors also was supported by the data on the effect of AH-6809 and AH-23848B on cyclin levels.…”
Section: Discussionmentioning
confidence: 77%
“…While the effects of PGE 2 on epidermal keratinocytes are reasonably well understood [1,[43][44][45], there has been much less investigation in the effects of PGE 2 on human melanocytes. Several years ago we set out to determine the biologic effects of PGE 2 on human melanocytes, and showed that nanomolar concentrations of PGE 2 stimulated melanocyte dendricity [7].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple subtypes of the PGE 2 receptor are expressed in cilary epithelial cells (48), osteoblastic cells (49), kerotinocytes (50), fibroblasts (23), and platelets (51). Furthermore, human Jurkat cells express both EP2 and EP4 receptors; however, the expression of EP2 receptor is ϳ100-fold lower than that of EP4 receptors (52).…”
Section: Discussionmentioning
confidence: 99%